Satisfaction in the provision of health services in older adults, Colombia 2018 (Revista Venezolana de Salud Pública, 2020)
The term active aging is relatively new and very little known, although much has been said about this in recent times. The objective of this work to review the literature on health care for the elderly. The method used a narrative review through an exploration of exploration of scientific articles in the databases: Science direct, Pubmed and Scielo. In the results it was found that in several articles the elderly were not satisfied with the care they received in health. In conclusion, as reported by older people, there is a large gap between what is said in public policies on aging and what is actually being done in the provision of services. Regarding the perception that older adults have of their health in Antioquia, there is a very high percentage that believes that health care is not adequate
Keywords: health; elder; greybeard; perception,; attention; public policies